2016
DOI: 10.1667/rr14400.1
|View full text |Cite
|
Sign up to set email alerts
|

Spaceflight-Relevant Challenges of Radiation and/or Reduced Weight Bearing Cause Arthritic Responses in Knee Articular Cartilage

Abstract: There is little known about the effect of both reduced weight bearing and exposure to radiation during spaceflight on the mechanically-sensitive cartilage lining the knee joint. In this study, we characterized cartilage damage in rat knees after periods of reduced weight bearing with/without exposure to solar-flare-relevant radiation, then cartilage recovery after return to weight bearing. Male Sprague Dawley rats (n = 120) were either hindlimb unloaded (HLU) via tail suspension or remained weight bearing in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…Joint loading on Earth is necessary to maintain structural integrity, proper function and homeostasis of cartilage and other tissues constituting load-bearing synovial joints (1,2). Thus, the reduced weight bearing experienced with spaceflight represents a substantial challenge to maintaining the health of synovial joints (3)(4)(5)(6). Clinically relevant structural degradation of cartilage has been documented after periods of prescribed partial-or nonweight-bearing (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Joint loading on Earth is necessary to maintain structural integrity, proper function and homeostasis of cartilage and other tissues constituting load-bearing synovial joints (1,2). Thus, the reduced weight bearing experienced with spaceflight represents a substantial challenge to maintaining the health of synovial joints (3)(4)(5)(6). Clinically relevant structural degradation of cartilage has been documented after periods of prescribed partial-or nonweight-bearing (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report suggesting that radiation worsens cartilage loss caused by HLU suggests that radiation has a compounding effect on cartilage destruction. 10 …”
mentioning
confidence: 99%
“…This cartilage has a limited regenerative capacity (Karuppal, 2017) and is important for absorbing load to protect the underlying bone, ensuring the smooth function of joints (Fox, Bedi and Rodeo, 2009). Human bed-rest studies, hind-limb unloading studies in rats and studies performed on mice exposed to real microgravity have demonstrated that loss of mechanical forces lead to cartilage degradation primarily through proteoglycan loss (Souza et al , 2012; Ganse et al , 2015; Willey et al , 2016; Fitzgerald et al , 2019). Cell culture experiments carried out in microgravity also support the observation of cartilage degradation under reduced loading conditions, with cytoskeletal reorganization and extracellular matrix (ECM) composition altered following short exposures (Van Loon et al , 1995; Freed et al , 1997; Zhang et al , 2003; Ulbrich et al , 2010; Aleshcheva et al , 2013).…”
Section: Introductionmentioning
confidence: 99%